A Literature Review of Scientific and STEAM Approach in 2013 and Merdeka Curriculum - Yuni Liana; Yudi Basuki (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2023)
A scientific approach is a learning process that is designed in such a way that students actively construct concepts, laws, or principles. Meanwhile, a STEAM approach is an integrated approach that combines science, technology, engineering, art, and mathematics as a means of developing student skills in the 21st century. The research aims to investigate and describe the crucial changes from the scientific approach in the 2013 curriculum to the STEAM approach in the Merdeka Curriculum. The research used is qualitative and focuses on documentary studies. The research instrument used observational field notes sourced from literature such as books, scientific journals, and reference books. The data were analyzed in a qualitatively descriptive way. The research Findings showed that there are several crucial changes from the scientific approach in the 2013 curriculum to the STEAM approach in the Merdeka Curriculum, namely in terms of objectives, principles, and learning stages.